Wujud Nilai Moral dalam Novel Sunset Bersama Rosie Karya Tere Liye: Kajian Sosiologi Sastra - Istina Rahmawati; Rukiyah Rukiyah; Fajrul Falah (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
The novel Sunset Bersama Rosie by Tere Liye presents a variety of moral values contained in each character. The purpose of this study is to reveal the form of moral values contained in the novel Sunset Bersama Rosie by Tere Liye. Data analysis is descriptive qualitative. The technique of presenting the results of data analysis is descriptive by presenting data in the form of explanations or descriptions. The results of this study indicate that there are three forms of moral values. The form of moral values in human relations with God includes praying and be grateful. The form of moral values in human relations with themselves, namely working hard, never giving up, being responsible, independent, and honest. The form of moral values in human relations with other people, namely respecting others, helping, being willing sacrifice, and grateful.